The role of readers' performance of a narrative on their beliefs about transgender persons: a mental models approach - Sharma, Neelam, author; Rouner, Donna, advisor; Aoki, Eric, committee member; Champ, Joseph, committee member; Kodrich, Kris, committee member; Sloane, Sarah, committee member (Colorado State University. Libraries, 2018)
Narratives are powerful communication tools that can influence people's beliefs and attitudes. Narrative processing literature explains cognitive operations involved in information processing in terms of transportation and identification with characters. Narrative performance, however, is an unexplored construct in social science narrative engagement literature. Narrative performance is a process by which readers bring cognitions and emotions to construct distinct story worlds into which they can be transported. This study advances the narrative processing literature by going beyond narrative transportation and by examining how people's performance of a narrative affects their story-related beliefs. A three-condition experiment, with 174 voluntary participants, was conducted at a large Western university to gauge the effects of performance on viewers' beliefs about transgender persons. Multivariate regression analysis demonstrates that narrative performance can weaken the effects of narrative transportation, and performance can be a stronger predictor of viewers' story-related beliefs. The study discriminates, using construct validity tests, narrative performance from narrative transportation, demonstrating construct validity. This study uses a mental models approach as a theoretical basis, and along with operationalizing narrative performance, develops valid and reliable scales for measuring viewers' beliefs about transgender persons and their propensity to take action in socializing with transgender persons.